Template-guided synthesis of Co nanoparticles embedded in hollow nitrogen doped carbon tubes as a highly efficient catalyst for rechargeable Zn-air batteries. (May 2020) - Zhou, Qingyan; Zhang, Zhen; Cai, Jiajun; Liu, Bing; Zhang, Yunlong; Gong, Xiaofei; Sui, Xulei; Yu, Aiping; Zhao, Lei; Wang, Zhenbo; Chen, Zhongwei
Abstract: Rational design and construction of highly efficient and durable non-noble-metal bifunctional catalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is crucial to promote the widespread implementation of rechargeable Zn-air batteries. Herein, a bifunctional catalyst comprising Co nanoparticles uniformly embedded in hollow nitrogen doped carbon tubes (Co@hNCTs) is fabricated by a facile tube-directed templating strategy. In this strategy, surfactant-treated polypyrrole (PPy) nanotubes serve as the structure-guiding templates for efficient capture of Co 2+, realizing the in-situ growth of zeolitic imidazolate frameworks-67 (ZIF-67) nanocrystals on PPy nanotubes. Sodium laurylsulfonate acts as anionic surfactant to endow PPy nanotubes with functional electronegative surface and strong anchoring effect toward ZIF-67, playing the pivotal role in binding of ZIF-67 nanocrystals with PPy nanotubes potently. Consequently, the developed catalyst presents a superior ORR activity with the half-wave potential of 0.87 V excellent durability with only a 7 mV loss of half-wave potential after 5000 cycles. The catalyst also exhibits superior catalytic performance for OER. When serving as an air electrode in Zn-air batteries, a large power density of 149 mW cm −2 and long-term cyclability for over 500 h are realized in ambient air, implying the great potential in practical application. Graphical abstract: One dimensional Co nanoparticles embedded in hollow nitrogen doped carbon tubes (Co@hNCTs) catalysts with hierarchical pore structure were successfully fabricated through a facile tube-directed templating strategy. The designed Co@hNCTs catalyst exhibits impressive bifunctional oxygen electrocatalytic performance for rechargeable Zn-air battery. Image 1 Highlights: Co nanoparticles uniformly embedded in hollow nitrogen doped carbon tubes. The sample exhibits high specific surface area with hierarchically pore structure. Polypyrrole nanotubes serve as skeleton to promote the dispersion of ZIF-67. Remarkable electrocatalytic activity and stability for ORR and OER.